Karykaturalny stereotyp zbrodni i przestępcy w węgierskiej kulturze lat realnego socjalizmu (1956-1989) = Caricature stereotype of crime and criminals in Hungarian culture in years of real socialism (1956-1989) - Nagy, László Kálmán (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the Hungarian crime-literature, and film at the time of Janos Kadar, ie. in the "Three T": "Tilt", "Tűr", "Tamogat" (in English translation PFS: prohibited, forbear, support), for ideological reasons belonged to a group of middle "T". In the years of socialism, when the crime was officially disappear, foreign detective books attracted great interest in Hungary.
Keywords: literatura węgierska; powieść kryminalna; realny socjalizm; 20 w.